GAMBARAN SANITASI DAN TINGKAT KEPADATAN LALAT DI WARUNG MAKAN KELURAHAN MAMBORO BARAT - Maryam Maryam; Fatmawati Fatmawati (CV. Adiba Aisha Amira, 2024)
Basic sanitation is a minimum environmental health requirement that every food stall must have to meet daily needs. Based on the initial survey on April 14 2022 which researchers carried out at several food stalls in the West Mamboro sub- district, we still found rubbish that was piled up and left open, and waste that was thrown directly on the ground, so that flies were still visible. The aim of the research is to determine the description of sanitation and the level of fly density in the temporary dumping area for food stalls in West Mamboro sub-district. This type of research uses descriptive research to determine the description of sanitation and the level of density of flies in temporary dumping places for food stalls in West Mamboro subdistrict. The results and conclusions were obtained that there were 50%/100% of food stalls that did not meet the requirements for waste management, there were also 80%/100% of food stalls that did not meet the requirements for waste management, for the level of fly density there were 10%/100% of stalls foods that fall into the solid category. It is hoped that food stall owners can manage waste and waste properly and also have the authorities inspect sanitation regularly.